Evaluasi Mutu dan Kandungan Proksimat Benih Padi Lokal Bangka Barat pada Penyimpanan dengan Metode Bermalai - Marini, Marini; Mustikarini, Eries Dyah; Kartika, Kartika (Universitas Sebelas Maret, 2025)
The success of rice production is largely determined by the quality of the seeds and proper management during storage. The study aims to evaluate the influence of storage methods on the quality of local rice seeds in West Bangka, as well as the chemical content of 8-month storage seeds. The method used is an experiment with a Complete Random Design (CRD) design. The main treatment is the storage method of seedling tubs and panicles. Six local rice accessions in Bangka, namely Mukot, Jawa, Ungu, Pulut Hitam, Balok Merah, and Mayang Hutan, were used as research materials. The observed characteristics include germination power, maximum growth potential, germination rate, and proximate content in seeds. The results showed that the storage method in the nursery was able to maintain the characteristics of germination, moisture content, vigor index, growth synchronicity and dry weight of normal sprouts. The storage method of panicles is able to maintain the characteristics of the seeds, such as maximum growth potential, germination rate and growth speed. Jawa rice accession is the accession that is most able to maintain seed quality with germination power (72.33%) and has better characters in parameters such as maximum growth potential, growth synchronicity, and germination rate after storage. Chemical content analysis showed that seeds stored using the bean sprout method had a more stable and lower moisture content than storage in a nursery tub. The carbohydrate content of seeds stored by the malai method is higher, which supports the germination process that requires high metabolism.